Minimally Invasive Selective Neck Dissection: A Prospective Study of Endoscopically Assisted Dissection via a Small Submandibular Approach in cT(1-2)N(0) Oral Squamous Cell Carcinoma - Fan, Song; Liang, Fa-Ya; Chen, Wei-Liang; Yang, Zhao-Hui; Huang, Xiao-Ming; Wang, You-Yuan; Lin, Zhao-Yu; Zhang, Da-Ming; Zhou, Bin; Chen, Wei-Xiong; Chai, Qiang; Wang, Hui-Jin; et al. (Springer, 2014)
Selective neck dissection (SND) in clinical N-0 (cN(0)) cases of oral squamous cell carcinoma (SCC) has been performed by surgeons using a retroauricular or modified facelift approach with robotic or endoscopic assistance. However, these procedures provide cosmetic satisfaction at the cost of possible maximal invasiveness. In this prospective study, we introduced and evaluated the feasibility as well as surgical invasiveness and cosmetic outcome of endoscopically-assisted SND via a small submandibular approach.Forty-four patients with cT(1-2)N(0) oral SCC (OSCC) were randomly divided into two groups of endoscopically-assisted SND and conventional SND. Perioperative and postoperative outcomes of patients were evaluated, including the length of the incision, operating time for neck dissection, estimated blood loss during the operation, amount and duration of drainage, total hospitalization period, total number of lymph nodes retrieved, satisfaction scores based on the cosmetic results, perioperative local complications, shoulder syndrome, and follow-up information.The mean operation time in the endoscopically-assisted group (126.04 +/- A 12.67 min) was longer than that in the conventional group (75.67 +/- A 16.67 min). However, the mean length of the incision was 4.33 +/- A 0.76 cm in the endoscopically-assisted SND group, and the amount and duration of drainage, total hospital stay, postoperative shoulder pain score, and cosmetic outcomes were superior in the endoscopically-assisted SND group. Additionally, the retrieved lymph nodes and complications were comparable.Endoscopically-assisted SND via a small submandibular approach had a longer operation time than the conventional approach. However, endoscopically-assisted SND was feasible and reliable while providing minimal invasiveness and satisfactory appearance.